2015
DOI: 10.1016/j.gaceta.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Hospital costs associated with nosocomial infections in a pediatric intensive care unit

Abstract: NI was associated with an increase in total cost, which implies that the prevention of these infections through specific interventions could be cost-effective and would help to increase the safety of healthcare systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
1
10
0
4
Order By: Relevance
“…These differences could be explained by different study populations, with more patients included after cardiac surgery, which may incur lower costs than medical or non-cardiac surgical paediatric ICU patients, and more patients with less organ failure, reflected by mean PeLOD of 7.5 as compared with a median PeLOD of 21 in our study. Third, Morillo-García et al reported higher costs for children with a nosocomial infection, as compared with those without a new infection [ 25 ], which supports our conclusion that healthcare costs can be reduced by preventing new infections.…”
Section: Discussionsupporting
confidence: 87%
“…These differences could be explained by different study populations, with more patients included after cardiac surgery, which may incur lower costs than medical or non-cardiac surgical paediatric ICU patients, and more patients with less organ failure, reflected by mean PeLOD of 7.5 as compared with a median PeLOD of 21 in our study. Third, Morillo-García et al reported higher costs for children with a nosocomial infection, as compared with those without a new infection [ 25 ], which supports our conclusion that healthcare costs can be reduced by preventing new infections.…”
Section: Discussionsupporting
confidence: 87%
“…The last 20 years have been characterized by the emergence and spread of antibiotic-resistant bacteria, which in turn have become a determining factor for the failure of antibiotic therapies, mainly in patients admitted to intensive care units (ICU). (1,2) This public health problem has serious implications on morbidity and mortality rates, and on public health systems stability, provided that both direct and indirect economic costs increase heavily due long-term hospitalizations and greater drug consumption. 3To date, different strategies have been developed to minimize the impact this public health problem can have on health systems, including appropriate antibiotics prescription, cleaning and disinfection programs, antimicrobial stewardship programs, and epidemiological surveillance of antimicrobial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Nosocomial infections (NI) have become a major problem in many neonatal intensive care units (NICUs) that complicate the hospitalization of patients and result in considerable morbidity and mortality, increased length of stay and increased health care costs. 4,5 The most frequent infections in NICUs are bloodstream infections, pneumonia, and necrotizing enterocolitis (NEC); less frequent complications are infections of the eyes, mouth or skin. 6,7 In developed countries, the incidence rate of nosocomial infections ranges from 6 to 9 infections per 1000 patient-days, with 3-to 20-fold higher rates in developing countries.…”
Section: Introductionmentioning
confidence: 99%